InGaN-Based microLED Devices Approaching 1% EQE with Red 609 nm Electroluminescence on Semi-Relaxed Substrates - Ryan C. White; Hongjian Li; Michel Khoury; Cheyenne Lynsky; Michael Iza; Stacia Keller; David Sotta; Shuji Nakamura; Steven P. DenBaars (Crystals, 2021)
In this paper, we report the successful demonstration of bright InGaN-based microLED devices emitting in the red spectral regime grown by metal organic chemical vapor deposition (MOCVD) on c-plane semi-relaxed InGaN substrates on sapphire. Through application of an InGaN/GaN base layer scheme to ameliorate high defect density and maintain appropriate lattice constant throughout the growth, high-In quantum wells (QWs) can be grown with improved crystal quality. Improvement to the design of the growth scheme also yields higher power output resulting in an increase to the external quantum efficiency (EQE). Combined, these two improvements allow for an 80 × 80 <semantics>μ</semantics>m<semantics>2</semantics> microLED device emitting at 609 nm to achieve 0.83% EQE. Furthermore, the true In content of the QW is measured using atomic probe tomography (APT) to confirm the improved In incorporation during high temperature active region growth. These developments represent advancement toward the realization of bright, highly efficient red III-nitride LEDs to be used in RGB applications under one material system.